Shaping hybrids – Form finding of new material systems. (June 2018) - Gengnagel, Christoph; La Magna, Riccardo; Ramsgaard Thomsen, Mette; Tamke, Martin
Form-finding processes are an integral part of structural design. Because of their limitations, the classic approaches to finding a form – such as hanging models and the soap-film analogy – play only a minor role. The various possibilities of digital experimentation in the context of structural optimisation create new options for the designer generating forms, while enabling control over a wide variety of parameters. A complete mapping of the mechanical properties of a structure in a continuum mechanics model is possible but so are simplified modelling strategies which take into account only the most important properties of the structure, such as iteratively approximating to a solution via representations of kinematic states. Form finding is thus an extremely complex process, determined both by the freely selected parameters and by design decisions.